PENENTUAN KOEFISIEN GESEKAN KINETIK KAYU PADA KAYU DENGAN METODE GRAFIS - Puji Hariati Winingsih (Universitas Sarjanawiyata Tamansiswa, 2016)
The aim of the reasearch is in order to determine the coefficient of kinetic friction in the wood by using graphical method through the experiment of friction force. To determine the coeeficient of wood kinetic friction by using variety of masses (12 x 10-1, 15 x 10-1, 22 x 10-1, 25 x 10-1, 27 x 10 1, 32 x 10-1, 36 x 10-1, 42 x 10-1, 46 x 10-1, 52 x 10-1) kg. The analysis of data used weighted linear regression with REGLIN which was written in Matlab language and run by the the Windows XP operation system. The outputs of regresion was obtained in the form of linear function coefficients are a0=0.0156 dan a1= 1.972, included the error (Sμ= 0.06). The results was revealed the coefficient of wood kinetic friction of the wood by using graphical method was μk= (0.20 ± 0.06). It was based on the theory that μk= 0.20. The chisqure test showed that there were relationships between fk and m, with the value of probability P ( 2 ÷ 2 ≥ ÷ hit ) = 50.16 %, so that the data was accepted.